GPD1L-A306del modifies sodium current in a family carrying the dysfunctional SCN5A-G1661R mutation associated with Brugada syndrome - Semino, Francesca; Darche, Fabrice Fernand; Bruehl, Claus; Koenen, Michael; Skladny, Heyko; Katus, Hugo; Frey, Norbert; Draguhn, Andreas; Schweizer, Patrick Alexander (Pflügers Archiv, 2024)
Loss-of-function variants of SCN5A, encoding the sodium channel alpha subunit Nav1.5 are associated with high phenotypic variability and multiple cardiac presentations, while underlying mechanisms are incompletely understood. Here we investigated a family with individuals affected by Brugada Syndrome (BrS) of different severity and aimed to unravel the underlying genetic and electrophysiological basis.
Online veröffentlicht: 1 December 2023
Gesehen am 18.01.2024